Monitoring of resistance of sourgrass to glyphosate herbicide in urban areas of the state of sÃo paulo, brazil - Gazola, T. [UNESP]; Dias, M. F. [UNESP]; Carbonari, C. A. [UNESP]; Velini, E. D. [UNESP] (FapUNIFESP (SciELO), 2019)
The objective of this work was to monitor the resistance of sourgrass (Digitaria insularis) to glyphosate in urban areas of the State of São Paulo to understand the spread of resistant biotypes. Three experiments were conducted under greenhouse conditions in a completely randomized design, with four replications. In the first experiment, seven sourgrass biotypes were used, and the control of plants was evaluated at 7, 14, 21, 28, and 35 days after application (DAA) of glyphosate. In the second experiment, the shikimic acid accumulation was quantified at 72 hours after the glyphosate application, and the same evaluations of weed control were performed. In the third experiment, rate-response curves were developed, with glyphosate at rates of 0, 90, 180, 360, 720, 1,440, 2,880, and 5,760 g a.e. ha-1 applied on three progenies obtained from self-fertilized seeds; the percentage of control and shoot dry weight of the plants were evaluated at 28 DAA to determine their resistance factor. The results confirmed the occurrence of biotypes of sourgrass resistant to glyphosate in urban areas of Ipaussu and Santa Cruz do Rio Pardo and transmission of this resistance to the progenies obtained from self-fertilized seeds. These results indicate the possibility of resistant sourgrass seeds to be transported and disseminated to other Brazilian regions, thus, contributing to increase cases of resistance of sourgrass to this herbicide. However, it should be confirmed by more detailed studies involving DNA and family trees to determine the genetic proximity between resistant biotypes from different regions, since independent selection may also occur.
Monitoramento da Resistência de Capim-Amargoso ao Herbicida Glyphosate em Áreas Urbanas do Estado de São Paulo
Keywords: Digitaria insularis; EPSPS; Resistance; Shikimic acid